QUESTIONING THE BENEFITS OF ARCHITECTURE WITH A USE AND IMAGE APPROACH - Susanti, Wiwik Dwi; Mutia, Fairuz; Elviana, Eva (Border: Jurnal Arsitektur, 2021)
The basic concepts of use and image introduced by Romo Mangun became the basis for harmonization in architecture that collaborated contextually with gatra elements. The phenomenon that occurs at this time is that many architectures are oriented to the image aspect, one of which is the emergence of thematic villages that have been transformed into tourist areas. It's like an oasis in the hustle and bustle of city life. The beautification carried out focuses on the physical aspect (image), the local character of the urban village is removed. Colorful thematic village in Malang City, the image aspect is more highlighted, while the use aspect is still questionable. The new facilities that have sprung up seem to eliminate the character of the urban village which is synonymous with heterogeneity. In this study, attempts to explore colorful villages with an image and use approach, because the village is identical with various kinds of problems that can be solved by architecture. The method used in this research is descriptive qualitative method. It is hoped that this research will be able to provide an illustration that in architecture it is not only emphasized on the image aspect but also with the use aspect.